Making Best Use of Every Healthcare Provider's Knowledge and Skills - Heather Mass (HealthcarePapers, 1999)
In "Organizing Primary Care for an Integrated System" Rosser and Kasperski propose changing the way family physicians practice to address deficiencies in the current primary-care delivery system in Canada. These deficiencies include a growing shortage of physicians, particularly in rural areas of Canada; the growing dependence of Canadians on acute hospital emergency units or "walk-in clinics" for primary care; fragmentation and unnecessary duplication in the delivery of primary-care services; lack of understanding on the part of the community and hospital sectors of the role of the family-practice physician; a fee-for-service funding model that does not reward prevention and health-promotion initiatives by physicians and makes high-volume, minorproblem visits the most lucrative; and lack of clarity with regard to what the public should expect from their physicians.